Research Progress of the Solid State Lithium-Sulfur Batteries - Wang, HangChao; Cao, Xin; Liu, Wen; Sun, Xiaoming (Frontiers in Energy Research, 2019)
Abstract：Lithium-sulfur batteries use lithium as the anode and sulfur as the cathode, which can achieve a theoretical energy density (2600 Wh.g-1) based on the chemical conversion reaction of 6Li + S8 ↔ 8Li2S several times higher than that of Li ion batteries The cost effectiveness together with the intrinsic high energy density makes Li-S batteries an important option for next generation energy storage. However, lithium-sulfur batteries using liquid electrolyte lead to the dissolution and "shuttle effect" of polysulfides, which greatly reduce the cycle life and specific capacity of the lithium-sulfur battery. In order to realize long cycle life, it is crucial to address the uncontrolled diffusion of polysulfides. Solid state lithium-sulfur battery, which replace liquid with solid electrolyte toaddress the polysulfide dissolution and diffusion problem, and at the same time which can effectively inhibit the growth of lithium dendrites on anode side, greatly improve the safety and cycle stability of lithium-sulfur batteries. In spite of all these merits, the performance and application of solid state Li-S batteries are strongly constrained by their low discharge capacity, poor rate performance and unsatisfied cycle life which need to overcome by advances in both materials and battery design. In this mini-review, we describe recent research progress of solid-state lithium-sulfur batteries from several aspects including sulfur-cathode design, different types of solid electrolyte and Li-S batteries based on them. New insights and synthesis approaches for stable lithium anode have also been summarized. We particularly emphasize the role of the interface in impeding battery reaction as well as the construction of the "solid/solid/solid" three-phase reaction boundary. At last, prospects and challenges in further advancing the scientific understanding and making the battery technology viable are presented to shine light on the upcoming research efforts.